Complete Genome Sequences of Six Human Bocavirus Strains from Patients with Acute Gastroenteritis in the North Region of Brazil - Watanabe, Aripuanã Sakurada Aranha (Genome Announc, 2018)
Human bocavirus (HBoV) is commonly associated with acute respiratory tract illness and gastroenteritis. We report six complete genomic sequences of HBoV strains from patients with gastroenteritis in Belém do Pará and Tocantins in the North Region of Brazil. Phylogenetic analysis indicated that the six HBoV strains belong to genotypes 1, 2, and 3.